Effect of Therapeutic Group Therapy on Self- Confidence among Adolescent with Orphanages in Mojokerto Regency - Siti Kholifah; Hendy Muagiri Margono; Rizki Fitryasari; Ah Yusuf (International Journal of Nursing and Health Services (IJNHS), 2020)
Adolescents living in orphanages have a negative impact on their emotional needs and psychosocial development. Lack of confidence in adolescent orphanages because of the lack of role of parents in assisting their development. This study aims to determine the effect of Therapeutic Group Therapy on the confidence of adolescents in orphanages. Method: The study design was Quasy experiment pre-post test control group design. The population in the study were 104 children who lived in orphanages A and B. The study samples were 62 adolescents who met the inclusion criteria, divided into 30 intervention groups and 32 control groups. The technique is obtained through purposive sampling. The independent variable is Therapeutic Group Therapy and the dependent variable is self-confidence. Data were obtained using a questionnaire and analyzed using the Wilcoxon Sign Ranks Test and Mann-Whitney U Test with a significance level of ? <0.05. Results: The results of the intervention group analysis showed the effect of TKT on self-confidence (p = 0,0001). The Mann-Whitney U Test results of the self-confidence test showed a value of p = 0,0001 (? <0.05) meaning that there was an effect of TKT on self-confidence between the two groups. Discussion and conclusions: The results of the study show that indicators of self-ability, responsibility and rationality increase higher than optimistic and objective. Increased self-esteem of orphanage adolescents due to TKT activities. Biological, psychosexual, moral, spiritual, cognitive, language, psychosocial, emotional, talent and creativity TKT stimulation provides a meaningful influence in increasing adolescent self-confidence. Therapeutic Group Therapy can increase the confidence of adolescents in orphanages